Knowledge and practice of menstrual hygiene among adolescent girls in secondary schools of Herat, Afghanistan - Odey, Goodness Ogeyi; Adegbite, Moriam Adesola; Razaqi, Nosaibah; Faizi, Gulalai; Afzali, Habibah; Ahmadi, Mozhgan; Frough, Zahra; Bhattacharya, Sudip; Lucero-Prisno III, Don Eliseo (Razi International Medical Journal, 2022)
Background: The experience of menarche is often confusing and causes ambivalence among adolescent girls due to their lack of information on the menstruation cycle and menstrual vaginal bleeding. This study aimed to assess the knowledge and practice of menstruation and menstruation hygiene in Afghanistan. Methods: This is a cross-sectional study using a survey questionnaire administered from 10 March 2021 to 15 April 2021 among secondary school girls in Herat, Afghanistan. It evaluated their knowledge of menstruation and menstrual hygiene practices. 768 girls responded to the survey. Data was encoded and statistically analysed using SPSS. Results: 53.3% of girls surveyed had a good knowledge of menstruation and menstrual hygiene. 15.9% of girls surveyed who did not experience menarche showed a good knowledge score. In terms of practice, 32.9% took a rest and missed school during menstrual bleeding. 2.1% of the participants mentioned that teachers were the first source of information on menstruation and menstrual hygiene. Conclusion: Knowledge of menstruation and menstrual hygiene among girls surveyed was lower than in other countries. Awareness campaigns regarding menstruation and menstrual hygiene are recommended. It is suggested to add a subject on these for secondary school girls to learn more and encourage them to openly discuss among themselves.